Freudian model of psyche and homosexual turning points in selected LGBT texts - Razali, Amirah (2017)
There have been numerous studies attempting to establish a genetic cause for homosexuality conducted since the early 1990’s that have not been proven to be either valid or reliable. To date, the quest to establish the existence of a single chromosome in human bodies that would identify a person’s homosexual identity seems futile, as there are no scientific findings or DNA results that prove that the third gender can be biologically determined. Therefore, on the premise that homosexuality, like race, is nurture rather than nature in the great nature versus nurture debate, this dissertation focuses to identify the turning points of homosexuality among eight individual lesbian, gay, bisexual and transsexual (LGBT) characters in eight selected short stories taken from four selected texts. The texts are Body 2 Body-A Malaysian Queer Anthology edited by Jerome Kugan and Pang Khee Theik (2009), Close Range: Wyoming Stories 1, written by Annie Proulx (2000), It’s Our Turn: A Collection of LGBT stories written by Zachary Perry LaPoint (2014) and Best Lesbian Love Stories 2005 edited by Angela Brown (2005). This dissertation will examine the eight selected individual characters’ feelings and decisions when they adapt an LGBT identity by explaining in detail with the application of Freudian model of psyches, which are relatively known as the Id, Ego and Superego in order to determine whether these characters’ Ids, as opposed to their Egos and Superegos, are actually taking control of their desires or whether it exists naturally from within the ego that they choose to become and remain part of the LGBT community. Through the findings, it has been revealed that there are certain signs of unconscious mind at work, which leads the characters to become LGBT individuals. The findings of this study may encourage future researchers to analyse further into the interpretations of turning points using a different psychoanalysis approach to depict any subliminal messages in a story.